Synthesis and In Vitro Antitumor Activity of Two Mixed-Ligand Oxovanadium(IV) Complexes of Schiff Base and Phenanthroline. (29th January 2013) - Zhang, Yongli; Wang, Xiangsheng; Fang, Wei; Cai, Xiaoyan; Chu, Fujiang; Liao, Xiangwen; Lu, Jiazheng
Abstract : Two oxovanadium(IV) complexes of [VO(msatsc)(phen)], (1 ) (msatsc = methoxylsalicylaldehyde thiosemicarbazone, phen = phenanthroline) and its novel derivative [VO (4-chlorosatsc)(phen)], (2 ) (4-chlorosatsc = 4-chlorosalicylaldehyde thiosemicarbazone), have been synthesized and characterized by elemental analysis, IR, ES-MS, 1 H NMR, and magnetic susceptibility measurements. Their antitumor effects on BEL-7402, HUH-7, and HepG2 cells were studied by MTT assay. The antitumor biological mechanism of these two complexes was studied in BEL-7402 cells by cell cycle analysis, Hoechst 33342 staining, Annexin V-FITC/PI assay, and detection of mitochondrial membrane potential (ΔΨm). The results showed that the growth of cancer cells was inhibited significantly, and complexes 1 and 2 mainly caused in BEL-7402 cells G0/G1 cell cycle arrest and induced apoptosis. Both 1 and 2 decreased significantly the ΔΨm, causing the depolarization of the mitochondrial membrane. Complex 2 showed greater antitumor efficiency than that of complex 1 .